Time to Move from Vertical to Horizontal Approach in our COVID-19 Response in Nigeria - Olayinka Ilesanmi; Aanuoluwapo Afolabi (Ital Publication, 2020)
The novel Coronavirus (COVID-19) has adversely affected the already weak health system in Nigeria. The choice of whether to use vertical or integrated approach in solving health problems is determined by the peculiarity of the challenges. Vertical programs imply a variety of specific interventions that have not been fully integrated into the health system. The COVID-19 response in Nigeria still operates almost a vertical approach which is headed by the Federal Government through the Nigeria Centre for Disease Control (NCDC). Vertical healthcare programs address health problems through the application of specific measure(s). However, vertical approach alone has proved insufficient in the containment and control of COVID-19. The health system with the integrated services option is required in the proper management of COVID-19. The development of strategies by policymakers is required in the integration of COVID-19 response into the national health system.